PUBLIC ACCEPTANCE TOWARDS DENGUE PREVENTION TECHNIQUES IN MALAYSIA: A SCOPING REVIEW - Nurul Hannan Ahmad Uma; Noor Sharizad Rusly; Nur Asmadayana Hasim; Yusnaini Md. Yusoff; Muhammad Firdaus Aziz (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This research aims to explore the public’s acceptance of dengue prevention techniques in Malaysia, specifically emphasizing alternative approaches like autocidal traps. It offers a recent review and analysis of previous researches, investigating the behavioral factors that impact public support for dengue control techniques. Online articles from Scopus, PubMed, Web of Science, Google Scholar, and UKMLibrary were used. The scoping review protocol was applied in this study. A total of 15 relevant articles published from 2019 to 2025 were filtered and grouped into three primary categories for review: conventional techniques (e.g., fogging, larviciding), alternative techniques (e.g., Wolbachia, GM mosquitoes, autocidal traps), and behavioral factors. Findings indicated that while knowledge, perceived effectiveness, risk perception, and trust in authorities significantly impact acceptance, alternative prevention techniques receive comparatively less public support due to limited awareness and engagement. Furthermore, many current studies lack a theoretical framework, which limits the depth of behavioral understanding. This review underscores the critical need for theory-based public health research to enhance community involvement, particularly in dengue hotspot areas like Klang Valley, and to guide future policies and strategies for dengue prevention.